The presidency in the era of 24-hour news - Cohen, Jeffrey E. (Book collections on Project MUSE., 2008)
The Presidency in the Era of 24-Hour News examines how changes in the news media since the golden age of television--when three major networks held a near monopoly on the news people saw in the United States--have altered the way presidents communicate with the public and garner popular support. - Publisher.